1997
DOI: 10.1126/science.277.5330.1296
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Island Area on Ecosystem Properties

Abstract: Aim. The aim behind this work is: (i) to review the work on Scots pine needle litter in order to construct a model for the decomposition process, from litterfall until a stable fraction is left, (ii) suggest a simple regulating mechanism for its sequestration of carbon. Focus will be on foliar litter of Scots pine and the genus Pinus. Discussion. The chemical composition of newly shed pine litter is in part determined by climate, e.g. mean annual temperature (MAT). Thus concentrations of nitrogen (N) are highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

37
555
3
6

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 552 publications
(611 citation statements)
references
References 24 publications
37
555
3
6
Order By: Relevance
“…In contrast to other studies in both tropical (Ewel 1976;Xuluc-Tolosa et al 2003) and boreal forests (Wardle et al 1997), we found that the leaves of successional tree species decomposed much more slowly than did those of old-growth forest species. Our results agree with those of Mesquita et al (1998), who also worked in central Amazonia and who reported decay rates of successional species that were 2.4-4.7 times lower than those of oldgrowth forest species.…”
Section: Effect Of Litter Typecontrasting
confidence: 55%
“…In contrast to other studies in both tropical (Ewel 1976;Xuluc-Tolosa et al 2003) and boreal forests (Wardle et al 1997), we found that the leaves of successional tree species decomposed much more slowly than did those of old-growth forest species. Our results agree with those of Mesquita et al (1998), who also worked in central Amazonia and who reported decay rates of successional species that were 2.4-4.7 times lower than those of oldgrowth forest species.…”
Section: Effect Of Litter Typecontrasting
confidence: 55%
“…Thus, secondary succession might be expected to coincide with slower decomposition rates as far as plant effects are concerned. This was recently supported by ecosystem-level evidence from 50 boreal islands that varied in successional stage owing to increasing lightning frequency with island size (Wardle et al, 1997b). Higher decomposition and N mineralization rates corresponded to larger island size and therefore with earlier succession.…”
Section: Ecosystem Consequencessupporting
confidence: 53%
“…Fire-based disturbance can lead to major shifts in a variety of environmental parameters that are likely to have large direct and indirect effects on the soil microbial community through niche-based processes. For example, fires typically result in an ephemeral pulse of ammonium (NH 4 þ ), creation of a reactive charcoal layer, and subsequent changes in pH (Peitikäinen et al, 2000;DeLuca and Sala, 2006;Wardle et al, 1997Wardle et al, , 1998. On the other hand, because fire causes large reductions in the standing soil microbial biomass (Hart et al, 2005;Wang et al, 2012), dispersal, which can be largely stochastic, may lead to an increase in the relative importance of neutral processes in early community assembly.…”
Section: Introductionmentioning
confidence: 99%